2007
DOI: 10.1007/s00380-006-0950-0
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatın improves endothelial function in patents with subclinical hypothyroidism

Abstract: Patients with subclinical hypothyroidism (SCH) have impaired endothelial function probably related to dyslipidemia. The present study compares the effects of simvastatin versus levothyroxine (LT-4) treatment on lipid profile and endothelial function in patients with SCH. Fifty-nine patients with newly diagnosed SCH were enrolled. Patients were randomized into 3 groups to receive no treatment (n = 19), LT-4 (n = 20), or simvastatin (n = 20). We measured endothelium-dependent vasodilation (EDV) and endothelium-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 35 publications
2
25
0
2
Order By: Relevance
“…Our results did not reveal any significant differences of LDL levels in patients in comparison to control group. Several studies revealed contemporary elevation of TC and LDL [36][37][38], although many studies could not detect any alterations of lipid profile in sHT patients in comparison to control group [39][40][41], exactly similar to our investtigation that we could not demonstrate any differences in lipid profile of sHT and control group. In spite of all that, our study detected significant differences in serum TG levels between before and after treatment groups so that TG levels decreased meaningfully after treatment.…”
Section: Discussionsupporting
confidence: 89%
“…Our results did not reveal any significant differences of LDL levels in patients in comparison to control group. Several studies revealed contemporary elevation of TC and LDL [36][37][38], although many studies could not detect any alterations of lipid profile in sHT patients in comparison to control group [39][40][41], exactly similar to our investtigation that we could not demonstrate any differences in lipid profile of sHT and control group. In spite of all that, our study detected significant differences in serum TG levels between before and after treatment groups so that TG levels decreased meaningfully after treatment.…”
Section: Discussionsupporting
confidence: 89%
“…This study was important in demonstrating the cellular and molecular effects of LT4 therapy on the atherosclerotic process. In contrast to these studies, Duman et al [18] observed no improvement in FMD after LT4 treatment in patients with SH. In some studies, TSH levels have been found to be inversely correlated with FMD value in SH patients [19,20].…”
Section: Discussionmentioning
confidence: 91%
“…Some data suggest that levothyroxine replacement therapy may exert a beneficial effect on total cholesterol (TC), LDL-C and other predictors of vascular risk in SCH [100]. Furthermore, it appears that in SCH, statins with or without levothyroxine, can improve endothelial function and reduce carotid intima media thickness, reliable markers associated with CVD risk [101]. However, statins may be related to muscle symptoms even in patients with SCH [102].…”
Section: Thyroid Diseases and Statin Intolerancementioning
confidence: 99%